Anti-adipogenic peptides from ark shell protein hydrolysate: Purification, identification and anti-adipogenic effect. (October 2021) - Ahn, Chang-Bum; Je, Jae-Young
Graphical abstract: Highlights: Ark shell protein hydrolysate (ASPH) by peptic hydrolysis with anti-adipogenic effect were prepared. Two anti-adipogenic peptides LLRLTDL (843.02 Da) and GYALPCDCL (954.13 Da) were identified. LLRLTDL and GYALPCDCL inhibited lipid accumulation and proinflammatory cytokines production. Enhanced antioxidant enzyme activities were contributed to reduced intracellular ROS generation. Abstract: Ark shell protein hydrolysates-derived peptides showing anti-adipogenic effect were purified and identified using consecutive chromatographic techniques and tandem mass spectrometry. Two anti-adipogenic peptides LLRLTDL (843.02 Da) and GYALPCDCL (954.13 Da) were found to be highly effective for lipid accumulation inhibition in mouse bone marrow-derived mesenchymal stem cells differentiation into adipocyte. The inhibitory activity of LLRLTDL and GYALPCDCL for lipid accumulation was 48.53 % and 46.22 % at 100 μM, respectively. During adipocyte differentiation, two anti-adipogenic peptides LLRLTDL and GYALPCDCL significantly inhibited intracellular reactive oxygen species (ROS) generation by 47.39 % and 49.77 % at 100 μM. In addition, LLRLTDL and GYALPCDCL treatment increased cellular antioxidant enzyme activities, including superoxide dismutase, catalase, and glutathione peroxidase. Moreover, LLRLTDL and GYALPCDCL suppressed proinflammatory cytokine productions, including tumor necrosis factor-α, interleukin-1β and -6. These results suggest that LLRLTDL and GYALPCDCL could modulate adipocyte differentiation and be useful as anti-obesity ingredients or functional foods.